OPTIMALISASI PRODUKTIVITAS PETERNAK BABI DI SULAWESI UTARA MELALUI RANCANG BANGUN MESIN PEMBERI PAKAN TERNAK OTOMATIS - Tineke Saroinsong (P3M Politeknik Negeri Indramayu, 2019)
The pig farmers in eastern Tawaang Village of North Sulawesi besides working as farmers, they also work as coconut farmers. So they have difficulties in dividing the task. As in feeding activity that are still done manually, so it takes a long time for this activity. To overcome this problem, the farmers need appropriate technology in the maintenance of pigs, especially the time to feed the cattle. The purpose of the community partnership program in eastern Tawaang village is to create an automatic pig feed system. The methods of implementation is begun by identifying the problem, the second is the design and manufacture of feed machine, the third is the feed machine trial, and the las is to provide training on the right operation and maintenance of the feed machine. The resuls of this community partnership program is to provide approriate technology in the form of automatic, regular, and scheduled pig feed machine in accordance with the number and age of livestock. Finally, the quality and quantity of pork production in eastern Tawaang village in particular and in North Sulawesi in general will increase, beside that the farmer can optimize the working time.